Social Capital and Community Learning Centers: A Systematic–Bibliometric Review - Mardin Manangin; Salahudin; Muslimin Machmud (IJE : Interdisciplinary Journal of Education, 2026)
This study examines the development of research on Pusat Kegiatan Belajar Masyarakat (PKBM) or community learning centers as social capital in equivalency education and community-based learning within the context of global social inclusion. The increasing attention toward lifelong learning, inclusive education, and community empowerment has positioned community learning centers as strategic institutions in addressing educational inequality and strengthening social participation. However, previous studies remain fragmented, context-specific, and largely dominated by empirical approaches without comprehensive intellectual mapping. This study aims to analyze the structure, trends, and dynamics of global research on PKBM, social capital, and community learning through a hybrid systematic-bibliometric review approach. The study employed a Systematic Literature Review based on the PRISMA framework combined with bibliometric analysis using VOSviewer. Data were collected from the Scopus database through a systematic keyword-based search strategy and analyzed using network, overlay, and density visualizations. The findings reveal that social capital, empowerment, community learning centers, integration, and social inclusion constitute the dominant themes within the research landscape. The study also demonstrates a significant shift from administrative and program-oriented approaches toward transformative, participatory, and community-based educational paradigms. Furthermore, the findings identify several underexplored areas, particularly related to digital transformation, institutional sustainability, educational outcomes, and community resilience. This study contributes theoretically by strengthening the integration between social capital theory and community-based education studies while providing a comprehensive intellectual mapping of global research trends. The findings also offer practical implications for inclusive education policies and future research development in community learning and lifelong education.